2005
DOI: 10.1111/j.1529-8817.2005.00224.x
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure in the Mediterranean Basin: A Y Chromosome Perspective

Abstract: SummaryThe Mediterranean region has been characterised by a number of pre-historical and historical demographic events whose legacy on the current genetic landscape is still a matter of debate. In order to investigate the degree of population structure across the Mediterranean, we have investigated Y chromosome variation in a large dataset of Mediterranean populations, 11 of which are first described here. Our analyses identify four main clusters in the Mediterranean that can be labelled as North Africa, Arab,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 61 publications
(108 reference statements)
10
34
0
Order By: Relevance
“…Within Europe, we observed a northwest-southeast frequency cline for R-M269, similar to those observed previously [10,11,37], from high frequencies in western Europe to lower frequencies in the east. Within haplogroup R-M269 we genotyped a newly characterized SNP, S127 (equivalent to L11), for which the distribution in Europe and the Near East, together with that of R-M269 and R-M269(xS127), are shown in figure 2.…”
Section: Resultssupporting
confidence: 90%
“…Within Europe, we observed a northwest-southeast frequency cline for R-M269, similar to those observed previously [10,11,37], from high frequencies in western Europe to lower frequencies in the east. Within haplogroup R-M269 we genotyped a newly characterized SNP, S127 (equivalent to L11), for which the distribution in Europe and the Near East, together with that of R-M269 and R-M269(xS127), are shown in figure 2.…”
Section: Resultssupporting
confidence: 90%
“…Accordingly, all reports agree in showing strong MSY differentiation between Iberia and North Africa (Capelli et al 2006b and references therein). The MSY picture in Iberia is dominated by haplogroups belonging to the R1*(xR1a) clade [hg1 þ hg22 (Rosser et al 2000) or Eu18 (Semino et al 2000a)].…”
Section: Iberiasupporting
confidence: 72%
“…Based on SNPs, populations facing the Mediterranean basin were clustered into three groupings (Capelli et al 2006b): Near Eastern Arab, Mediterranean and North African. The observed pattern was ascribed to the Neolithic demographic expansion and subsequent westward migration by Phoenicians and Greeks that contributed to the distribution of Y chromosome types of most likely Near East origin.…”
Section: Europe: the Coarse Picturementioning
confidence: 99%
“…A previous investigation 25 showed that misassignment would influence only a minimal fraction of the haplotypes and so this can be assumed to have a negligible effect on our estimates. A Sicilian population was also included (samples overlapping in references 26,27 ). Sicilian genotypes were screened for E1b1b1* and J*(xJ2) lineages, and did not include DYS439.…”
Section: Samplesmentioning
confidence: 99%